Pengaruh Integrasi Artificial Intelligence dan Media YouTube dalam Pembelajaran Pendidikan Agama Islam terhadap Prestasi Belajar Siswa di SMK Plus Qurrota A’yun Garut - Ahmad Najib Komarudin; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
In the increasingly digitalised landscape of vocational education, Islamic Religious Education faces challenges in maintaining methodological relevance and learning effectiveness, particularly within technically oriented schools. This study aims to examine the impact of integrating Artificial Intelligence (AI), optimised through the YouTube platform, on students’ cognitive learning achievement in Islamic Religious Education at SMK Plus Qurrota A’yun, Garut Regency. The research is grounded in the pedagogical transformation required in the Society 5.0 era, where vocational students demand learning approaches aligned with their digital ecosystem while remaining rooted in Islamic spiritual values. A quasi-experimental pretest–posttest control group design was employed, involving 100 Year 11 students divided into an experimental group and a control group. The technological intervention utilised Large Language Models for pedagogical script development and Generative AI for content visualisation, distributed via YouTube. Statistical analysis using an independent t-test revealed a significant post-treatment difference between the two groups. The experimental group demonstrated a substantial increase in mean scores, a large effect size (d = 1.43), and a high level of student engagement. These findings indicate that the integration of AI and YouTube reduces cognitive load when learning abstract religious concepts, enhances information retention, and offers an effective blended learning model. The study concludes by recommending the adoption of adaptive curricula that position technology as a catalyst for religious understanding while preserving the teacher’s authoritative role.ABSTRAKDalam lanskap pendidikan vokasi yang semakin terdigitalisasi, Pendidikan Agama Islam (PAI) menghadapi tantangan relevansi dan efektivitas metodologis, khususnya di sekolah kejuruan yang lekat dengan ekosistem teknologi. Penelitian ini bertujuan untuk mengidentifikasi pengaruh integrasi teknologi Artificial Intelligence (AI) yang dioptimalkan melalui platform YouTube terhadap prestasi belajar kognitif siswa pada mata pelajaran PAI di SMK Plus Qurrota A’yun, Kabupaten Garut. Penelitian dilandasi urgensi transformasi pedagogis di era Society 5.0, yang menuntut pendekatan pembelajaran selaras dengan karakteristik digital siswa tanpa mengabaikan nilai spiritual Islam. Metode yang digunakan adalah kuasi-eksperimental dengan desain pretest–posttest kelompok kontrol, melibatkan 100 siswa kelas XI yang dibagi ke dalam kelompok eksperimen dan kontrol. Intervensi dilakukan melalui pengembangan video pembelajaran berbasis YouTube yang dioptimalkan menggunakan Large Language Models untuk penyusunan skrip pedagogis dan Generative AI untuk visualisasi konten. Hasil analisis uji-t independen menunjukkan perbedaan signifikan antara kedua kelompok setelah perlakuan, dengan peningkatan skor rata-rata yang tinggi pada kelompok eksperimen serta ukuran efek besar (d = 1,43) dan tingkat keterlibatan siswa yang tinggi. Temuan ini menyimpulkan bahwa integrasi AI dan YouTube efektif dalam menurunkan beban kognitif, meningkatkan retensi pemahaman materi PAI yang abstrak, serta mendukung model blended learning yang adaptif.